Manajemen Waktu Mahasiswa Pendidikan Ekonomi dalam Menyeimbangkan Akademik, Kualitas Tidur - Isma Dwi Ardiyanti (Universitas Pendidikan Ganesha, 2025)
This study aims to explore how students of the Economics Education Study Program at Surabaya State University manage their time to balance academic demands and the need for optimal sleep quality. The main focus of this study is to uncover strategies, challenges, and the impact of time management on students' academic well-being and sleep health. This study uses a descriptive qualitative approach with an ethnographic design. Data were collected through an online questionnaire distributed to 12 active students in semesters 4–6 and analyzed using NVivo 12 software. The analysis process was carried out using inductive coding techniques and visual modeling in the form of word clouds and treemaps to identify dominant themes in students' time management. The results show that words such as